Beyond Better Wine: The Impact of Experiential and Monetary Value on Wine Tourists' Loyalty Intentions. Issue 2 (1st February 2016) - Chen, Xiaoyu; Goodman, Steve; Bruwer, Johan; Cohen, Justin
Abstract : Research on the experiential aspects of wine tourism has been advocated but the evolution of this approach in this field is still in its infancy. This exploratory study proposes a behavioral model to simultaneously examine the role of hedonic and utilitarian shopping value as well as monetary value perceptions in predicting cellar door visitors' overall satisfaction and loyalty intentions. The application of partial least squares path modeling indicates that cellar door visitors are oriented toward the experiential aspects of the visit itself as much as to pragmatic considerations in purchasing wine. The insights are, therefore, directed toward the creation of a total cellar door experience. These findings contribute to the understanding of a cellar door visitors' decision-making process, providing managers and researchers with insights into how to effectively accommodate cellar door visitors' needs.